Putting the world in the world wide web: the globalisation of the internet. (1st December 2006) - Shea, Timothy; Ariguzo, Godwin; White, D. Steven
Without question, the first decade of the internet as a mass communications platform belonged to the USA. US universities, businesses and users dominated the online landscape to the point that English became the language of choice of the world wide web. However, as internet technology and access diffuses to more countries, will US dominance of the internet continue? The authors argue that one tipping point has already occurred – the majority of users on the internet today are non-native English speakers. The next tipping point, not too far away, is when non-native English speakers conduct the majority of e-commerce. The paper discusses internet usage trends, including language, diffusion models and the challenges facing businesses figuring out when and how to effectively compete in the trillion dollar e-commerce marketplace. This paper concludes with research opportunities.